A Range Extension of Anemonastrum trullifolium (Hook.f. & Thomson) Mosyakin (Ranunculaceae) to Pir Panjal range of Western Himalaya - Rajput, Pravesh; Yadav, Rekha; Agnihotri, Priyanka (Indian Forester, 2023)
No Abstract.